Covariance stability test for exploring the impact of subprime financial crisis on the FOREX - Olusegun, Alo; Sharif, Shamshuritawati (MAXWELL Science Publication, 2016)
The sub-prime crisis started from November 2006 to February 2008 is a global crisis that affected almost all economy activities in the world. In this study, we used the covariance stability test for exploring its impact towards foreign exchange rate among 15 currencies. Box’s M control chart and its root causes analysis are employed to understand the behaviour and interrelationship of FOREX’s structure among America and Europe continents. From the analysis, it shows that the structures of covariance from Jan, 2006 to Dec, 2008 are not stable.To be detail, if there is any shift on USD during April-June 2007, the nearest currencies that will received the impact are Argentine Peso, Chilean Peso and Rusia Ruble.